Analisis Kurikulum Merdeka dalam Perspektif Filsafat Pendidikan Progresivisme - Mutik Hidayat; Muhlis Muhlis; Dania Dyah Fitrawan (Dimar Jaya Publishing, 2025)
The Kurikulum Merdeka is a strategic effort to improve the quality of education and foster independence in students' thinking and expression. This study discusses how the Kurikulum Merdeka is implemented from the perspective of progressive education philosophy. This study aims to analyze the implementation of the Kurikulum Merdeka from the perspective of progressive education philosophy. This research method uses qualitative research and a library research approach. The results of the study show that the Merdeka Curriculum is in line with the philosophy of progressivism, especially in the application of project-based learning, differentiated learning, strengthening the Pancasila Student profile, and the role of teachers as learning facilitators. This curriculum encourages students to be active, creative, and reflective in dealing with contextual problems.